The RIGMA model as a valuable tool for evaluating teachers’ technological advancement in distance education - Cichoń, Małgorzata; Sypniewski, Jakub; Piotrowska, Iwona (Quaestiones Geographicae, 2024)
The study aims to develop a model for evaluating the technological advancement of teachers engaged in distance education, with variations explained by their individual attributes. These attributes encompass organization skills, adaptation, communication abilities, independence, proficiency, efficiency, and attitude towards distance education. The study involved surveys conducted on 130 geography teachers in Poland during the initial months of the pandemic. The authors hypothesized that the variability in technological advancement could be attributed to the functional capabilities of maps used in geography lessons and the identified personal characteristics. To test these assumptions, 25 original indicators were devised, forming the Technological Advancement Index (TAI). Through statistical analysis, a disparate technological advancement among teachers was observed, with TAI scores ranging from +6.0 to −10.60. At the lower proficiency levels, variability was primarily linked to independence, followed by proficiency and efficiency. As advancement levels increased, so did the functional diversity of maps used, particularly in problem-solving and the creation of new digital maps. This exploration into technological advancement yielded novel conceptual and empirical insights, allowing validation of the Substitution, Augmentation, Modification, Redefinition (SAMR) model used in traditional education. Additionally, it led to development of the Recommendation, Imitation, Gamification, Mobilization, Action (RIGMA) model tailored for distance education. The proposed model holds applicability in enhancing geographic education during distance learning initiatives.